A genome resource for Acacia, Australia’s largest plant genus - Todd G. B. McLay; Daniel J. Murphy; Gareth D. Holmes; Sarah Mathews; Gillian K. Brown; David J. Cantrill; Frank Udovicic; Theodore R. Allnutt; Chris J. Jackson (PLoS ONE, 2022)
Acacia (Leguminosae, Caesalpinioideae, mimosoid clade) is the largest and most widespread genus of plants in the Australian flora, occupying and dominating a diverse range of environments, with an equally diverse range of forms. For a genus of its size and importance, Acacia currently has surprisingly few genomic resources. Acacia pycnantha, the golden wattle, is a woody shrub or tree occurring in south-eastern Australia and is the country’s floral emblem. To assemble a genome for A. pycnantha, we generated long-read sequences using Oxford Nanopore Technology, 10x Genomics Chromium linked reads, and short-read Illumina sequences, and produced an assembly spanning 814 Mb, with a scaffold N50 of 2.8 Mb, and 98.3% of complete Embryophyta BUSCOs. Genome annotation predicted 47,624 protein-coding genes, with 62.3% of the genome predicted to comprise transposable elements. Evolutionary analyses indicated a shared genome duplication event in the Caesalpinioideae, and conflict in the relationships between Cercis (subfamily Cercidoideae) and subfamilies Caesalpinioideae and Papilionoideae (pea-flowered legumes). Comparative genomics identified a suite of expanded and contracted gene families in A. pycnantha, and these were annotated with both GO terms and KEGG functional categories. One expanded gene family of particular interest is involved in flowering time and may be associated with the characteristic synchronous flowering of Acacia. This genome assembly and annotation will be a valuable resource for all studies involving Acacia, including the evolution, conservation, breeding, invasiveness, and physiology of the genus, and for comparative studies of legumes.